Political aspects of qualitative methodology in a critical perspective: towards participatory research-activities (Participatory Action Research) - Granosik, Mariusz (Methodological critique in the practice of knowledge creation, 2019)
By adopting the basic assumptions of a “knowledge-based society”, the methodology of scientific research can be considered as a kind of political system. It provides procedures for determining who (sampling) and to what extent (the method of data interpretation) has the right to co-create knowledge and therefore society. In this perspective, all research activities, and in particular social research, have a political character. In the text, methodological assumptions and qualitative research procedures are discussed from the perspective of their political consequences. This issue seems to be so important that, as a result, there is an uneven participation in the production of knowledge of representatives of various social classes. The chapter ends with a proposal for a change in the paradigm of qualitative research towards their “full participation”.